DEKONSTRUKSI MITOS KEHAMILAN DI KABUPATEN PADANG PARIAMAN - Muhammad Yunis (Universitas Andalas, 2010)
This study aimed to decontruct, elaborate, expres, doing signification, eksplorate, and to transfigurate the pregnancy speaking at myth Padang Pariaman Regency. There is five significant problems, namely (1) to elaborat the form of pregnancy myth speaking, (2) to represent the function of the pregnancy myth speaking, (3) to signify the pregnancy myth speaking, (4) to eksplore the pregnancy myth speaking, and (5) to transfigurate the pregnancy myth speaking. Relate to myth narrative decontruction, the writer uses two methods: (1) the field research; and (2) doing intervieu with Padang Pariaman Regency society, that is Sintoga District, Nan Sabaris District, 2x11 VI Lingkuang District, and Lubuak Alung District. To support the analysis the writer needs some theoried they are speech act, semiotic, hypersemiotic, and desire philosophy.The elaboration form is projected by the meaning which is squarely at the text of pregnancy speaking myth. The step of representation function projected with analyzing function philosophy pregnancy myth speaking for society who produces the myth. Both of significations are called with form is the referred as with form projection and function of pregnancy myth speech. At signification form is the primary step of meaning which is closed to the theory about sign, that is semiotic. For the eksploration step is related to define the secondary stpe, which is closed to the hyersemiotic theory. Eksploration step is related to intertext study. It is aimed to describe ‘’the other meaning’’ of language sign which resulted in the myth speech The transfiguration step is described as the evaluation values which closed to the willingness philosophy.